Cell Biology, Genetics, and Biochemistry for Pre-Clinical Students - LeClair, Renee (Open textbook library., 2021)
Cell Biology, Genetics, and Biochemistry for Pre-Clinical Students is an undergraduate medical-level resource for foundational knowledge across the disciplines of genetics, cell biology and biochemistry. This USMLE-aligned text is designed for a course in first-year undergraduate medical course that is delivered typically before students start to explore systems physiology and pathophysiology. The text is meant to provide the essential information from these content areas in a concise format that would allow learner preparation to engage in an active classroom. Clinical correlates and additional application of content is intended to be provided in the classroom experience. The text assumes that the students will have completed medical school prerequisites (including the MCAT) in which they will have been introduced to the most fundamental concepts of biology and chemistry that are essential to understand the content presented here. This resource should be assistive to the learner later in medical school and for exam preparation given the material is presented in a succinct manner, with a focus on high-yield concepts. The 276-page text was created specifically for use by pre-clinical students at Virginia Tech Carilion School of Medicine and was based on faculty experience and peer review to guide development and hone important topics. Instructors reviewing, adopting, or adapting parts or the whole of the text are requested to register their interest at: https://bit.ly/interest-preclinical. Instructors and subject matter experts interested in and sharing their original course materials relevant to pre-clinical education are requested to join the instructor portal at https://www.oercommons.org/groups/pre-clinical-resources/10133. Suggested Citation LeClair, Renée J., (2021). Cell Biology, Genetics, and Biochemistry for Pre-Clinical Students, Blackburg, VA: Virginia Tech Publishing. https://doi.org/10.21061/cellbio. Licensed with CC BY NC-SA 4.0.